Integration of Social Studies Learning with Applied Islamic Values Through Smart Card Media at MTs. NU Raudlatut Tholibin Kudus - Misroh Sulaswari; Eva Banowati; Suyahmo Suyahmo; Eko Handoyo (International Conference on Science, Education, and Technology, 2023)
This study aims to describe social studies learning integrated with applied Islamic values ​​through smart card media at MTs. NU Raudlatut Tholibin Kudus, identifying supporting and inhibiting factors, knowing the responses of teachers and students. Using a qualitative descriptive approach through the action research method in collaboration with social studies teachers, this research practices social studies learning integrated with applied Islamic values ​​which has never been done before. Data was collected through observation, interviews and FGD, analyzed through data reduction, data presentation, and drawing conclusions. The results showed that there were four stages in social studies learning integration, namely the preparation stage, the organizing stage, the presentation stage, and the conclusion drawing stage. Identification of supporting factors, namely: support for madrasah institutions, students from Islamic boarding schools, interesting smart card media, and active and fun learning activities. Inhibiting factors include the lack of understanding of students, easily damaged smart card media, lack of classroom management, and the large number of tools in integrated learning. In general, the response obtained was positive except for students who had a negative response because some students were less interested in social studies subjects which were considered difficult and memorized a lot. Teacher creativity is needed in an effort to create fun learning. Teacher creativity will create meaningful and quality learning.